Network Screening for Smarter Road Sites: A Regional Case - Grieco, Attila; Montaldo, Chiara; Occelli, Sylvie; Tarditi, Silvia (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Road safety has been a main societal and policy issue in many European countries since the early years of last decade. After the 2000-2010 Road Safety Programme launched by the European Commission, in 2011 the Commission adopted the new 2020 programme, even more demanding than the previous. As the societal consequences of road casualties are increasingly perceived as a core dimension of smart mobility, road safety system is now facing new challenges. Current mobility shifts to softer and greener transportation means raise new safety concerns for an increasingly larger share of vulnerable road users. The need to integrate road safety requirements with other residential, mobility, and environmental policies calls for a more detailed understanding of the phenomenon at different spatial levels and with different observation lenses. The pilot study described in this paper is a contribution to this end. It aims at identifying the accident prone sites of the regional road network to help prioritizing safety interventions, by the regional administration having road planning responsibilities. The study develops a screening approach to select hazardous road locations, outside urban premises, from the Piedmont provincial and state roads. The most recent data for the 2010-2012 years were considered, drawn from the ISTAT road accident database, managed by the CMRSS. The procedure consists of the following steps: identification of the elementary road sections to be screened, through a GIS analysis; definition of the screening groups (road sections have been subdivided in 4 length classes); definition of the selection criteria, with two severity thresholds based on the crash density; classification of the elementary road sections by severity thresholds.